2006
DOI: 10.1093/jn/136.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors and Socioeconomic Indicators Are Associated with Household Food Insecurity among Pregnant Women

Abstract: Household food insecurity has been associated with several negative health outcomes, yet little is known about the prevalence and correlates of household food insecurity during pregnancy. This study was conducted as part of the Pregnancy, Infection, and Nutrition prospective cohort study to identify risk factors of preterm birth. The USDA 18-item scale was used to assess the prevalence of food insecurity among pregnant women with incomes Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
236
6
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(266 citation statements)
references
References 33 publications
18
236
6
6
Order By: Relevance
“…Other potential determinants of food insecurity include belonging to an ethnic minority (10,(16)(17)(18) , having a lower level of education (10,(15)(16)(17) , being of younger age (16,19) and family type (single-parent family v. couples with children) (9,10,14,20) . Food insecurity may be associated with lower fruit and vegetable intakes (21)(22)(23)(24)(25) , lower consumption of lean meats (21,23) , poorer general health (13,20,21,23,(26)(27)(28)(29) , chronic conditions such as CVD (20,(30)(31)(32) and depression (26,27,(33)(34)(35)(36)(37) , and overweight or obesity among women (38)(39)(40)(41)(42)(43)(44) . There are several hypothesised mechanisms through which food insecurity may be associated with th...…”
mentioning
confidence: 99%
“…Other potential determinants of food insecurity include belonging to an ethnic minority (10,(16)(17)(18) , having a lower level of education (10,(15)(16)(17) , being of younger age (16,19) and family type (single-parent family v. couples with children) (9,10,14,20) . Food insecurity may be associated with lower fruit and vegetable intakes (21)(22)(23)(24)(25) , lower consumption of lean meats (21,23) , poorer general health (13,20,21,23,(26)(27)(28)(29) , chronic conditions such as CVD (20,(30)(31)(32) and depression (26,27,(33)(34)(35)(36)(37) , and overweight or obesity among women (38)(39)(40)(41)(42)(43)(44) . There are several hypothesised mechanisms through which food insecurity may be associated with th...…”
mentioning
confidence: 99%
“…Women's responsibilities in managing family feeding (7) , gender bias in the experience of FI (8) and unequal control over household resources make them particularly vulnerable to FI and its consequences (3) . Data from the USA indicate that, when faced with FI, women suffer a range of negative nutritional (9) and psychosocial consequences (10,11) .Pregnant women are more likely to experience greater FI than non-pregnant women because they have higher nutrient demands, less physical ability to obtain and prepare food (especially later in pregnancy and early postpartum) and less ability to engage in income-generating labour (10) . The three studies to date about FI among pregnant women have shown that FI has serious negative nutritional and psychosocial impacts on women's health (9)(10)(11) .…”
mentioning
confidence: 99%
“…Data from the USA indicate that, when faced with FI, women suffer a range of negative nutritional (9) and psychosocial consequences (10,11) .…”
mentioning
confidence: 99%
See 2 more Smart Citations